POSITION OF CEE AND HUNGARY ON THE GLOBAL SHARED SERVICE DELIVERY MARKET - Marciniak, Robert (European Scientific Journal, ESJ, 2013)
There are a lot of benefits of shared service model for any companies using it. Those companies could be successful that have size enough because for example cost-benefits depend on economies of scale. According to SunGard global research in 2010, 54% of companies using shared service centers have 1 billion or more US dollar turnover per a year. Because the larger a company, the larger the likelihood that the company use different separated systems, non-standardized processes. The main benefits of model are available not only in case of big volume exploited but diminishing redundancies. In this part of my research I am focusing on Central-Eastern Europe region and Hungary to analyze their position on the global service market. I found what are the most tendencies, which countries have good, which have worse positions in the global rankings and what will be in the future. I analyzed the effect of global crisis on the service delivery market and the recovery from it.